2012
DOI: 10.3892/ijo.2012.1479
|View full text |Cite
|
Sign up to set email alerts
|

Association of amphiregulin with the cetuximab sensitivity of gastric cancer cell lines

Abstract: The therapeutic activity of the epidermal growth factor receptor (EGFR)-directed monoclonal antibody cetuximab in gastric cancer is currently being investigated in clinical studies. Reliable biomarkers for the identification of patients who are likely to benefit from this treatment are not available. In this study, we assessed the activity of cetuximab in five gastric cancer cell lines (AGS, AZ521, Hs746T, LMSU and MKN1). The viability of two of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 47 publications
5
51
0
Order By: Relevance
“…Recent clinical trials have been designed with molecular alterations of cMET, EGFR/RAS/RAF as biomarkers (56,61,84). Future clinical trials may also assess molecular derangements such as cMET mutation, K-ras amplification, EGFR and HER2 status as predictive markers (14,15,83,84,86).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent clinical trials have been designed with molecular alterations of cMET, EGFR/RAS/RAF as biomarkers (56,61,84). Future clinical trials may also assess molecular derangements such as cMET mutation, K-ras amplification, EGFR and HER2 status as predictive markers (14,15,83,84,86).…”
Section: Resultsmentioning
confidence: 99%
“…cMET activation may mediate resistance to EGFR and HER2 in gastric cancer (14,15). Another study observed that the acquisition of a mutation in the MET activation loop (Y1230), destabilized the autoinhibitory conformation of MET and abrogated an important aromatic stacking interaction with the inhibitor (84).…”
Section: Resistance To Cmet Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aberrant signaling of MET by overexpression or gene amplification has been detected and correlated with tumor progression or patients' survival in GC [12][13][14][15] . Alternative activation of the MET pathway is considered an important mechanism causing resistance to treatments targeting HER family members [16,17] .…”
Section: Introductionmentioning
confidence: 99%
“…However, EGFR TKIs showed no significant clinical benefits in a phase II clinical trial in patients with SCLC (23). Indeed, the response to monoclonal EGFR antibodies can be predicted by the AREG secretion in gastric cancer cell lines (24).…”
Section: Cetuximab (Cet) Restored the Sensitivity To Amrubicinol (Amentioning
confidence: 99%